Pattern of global spin alignment of ϕ and K*0 mesons in heavy-ion collisions - STAR Collaboration (Nature, 2023)
Notwithstanding decades of progress since Yukawa first developed a description of the force between nucleons in terms of meson exchange1, a full understanding of the strong interaction remains a considerable challenge in modern science. One remaining difficulty arises from the non-perturbative nature of the strong force, which leads to the phenomenon of quark confinement at distances on the order of the size of the proton. Here we show that, in relativistic heavy-ion collisions, in which quarks and gluons are set free over an extended volume, two species of produced vector (spin-1) mesons, namely ϕ and K*0, emerge with a surprising pattern of global spin alignment. In particular, the global spin alignment for ϕ is unexpectedly large, whereas that for K*0 is consistent with zero. The observed spin-alignment pattern and magnitude for ϕ cannot be explained by conventional mechanisms, whereas a model with a connection to strong force fields2–6, that is, an effective proxy description within the standard model and quantum chromodynamics, accommodates the current data. This connection, if fully established, will open a potential new avenue for studying the behaviour of strong force fields. © 2023, The Author(s), under exclusive licence to Springer Nature Limited.
Keywords: dept.phy; peer-reviewed